Family caregivers' level of mastery predicts survival of patients with glioblastoma: A preliminary report. Issue 5 (27th October 2016) - Boele, Florien W.; Given, Charles W.; Given, Barbara A.; Donovan, Heidi S.; Schulz, Richard; Weimer, Jason M.; Drappatz, Jan; Lieberman, Frank S.; Sherwood, Paula R.
Abstract : BACKGROUND: Glioblastoma multiforme (GBM) is associated with a poor prognosis, and patients rely heavily on family caregivers for physical and emotional support. The capability and mental health of family caregivers may influence their ability to provide care and affect patient outcomes. The objective of the current study was to investigate whether caregivers' anxiety, depressive symptoms, burden, and mastery influenced survival in a sample of patients newly diagnosed with GBM. METHODS: Baseline data from caregiver‐patient dyads participating in a longitudinal study funded by the National Institutes of Health were used. Cox regression analyses were performed to determine whether caregiver anxiety (Profile of Mood States‐Anxiety), depressive symptoms (Center for Epidemiologic Studies–Depression Scale), burden (Caregiver Reaction Assessment), and feelings of mastery (Mastery Scale) predicted the survival time of patients with GBM after controlling for known covariates (patient age, Karnofsky performance status, type of surgery, and postsurgical treatment). RESULTS: A total of 88 caregiver‐patient dyads were included. The median overall survival for the sample was 14.5 months (range, 0‐88 months). After controlling for covariates, caregiver mastery was found to be predictive of patient survival. With each unit increase in mastery, there was a 16.1% risk reduction in patient death (95% confidence interval, 0.771‐0.913; P <.001). CONCLUSIONS: To the authors' knowledge, the results of the current study are among the first to explore the impact of family caregiving on the outcomes of patients with GBM. If these results are supported in other studies, providing neuro‐oncology caregivers with more structured support and guidance in clinical practice has the potential to improve caregivers' feelings of mastery, thereby influencing patients' well‐being for the better. Cancer 2017;123:832–40. © 2016 American Cancer Society . Abstract : In the current study, the authors investigate whether caregivers' anxiety, depressive symptoms, burden, and mastery influence survival in a sample of patients newly diagnosed with glioblastoma multiforme. After controlling for known covariates, caregiver mastery appears to be predictive of patient survival.